The interplay between culture, creativity, and tourism in the sustainable development of smaller urban centres - Tomaz, E. (2022)
At the end of the 1970s, cities and regions started to mobilize culture in order to boost local economic and social revitalization; since the 1990s, creative-based strategies have also become part of this development agenda. Culture- and creative-led planning is thought to offer distinctive and innovative solutions, products, and activities to attract residents, visitors, and investments. In the new millennium, tourism has become an integral part of these development strategies, with local providers identifying and exploiting distinctive endogenous cultural assets. In the context of the global village and the economic competition its endless possibilities engender, attempts at economic diversification and the expansion of innovation have also brought creativity to the tourism strategy design. Duxbury’s chapter in this volume, for example, shines a light on Portugal’s approach. Research literature in this field, however, tends to focus on large cities, neglecting the importance and innovative potential of smaller communities. To address that gap, this chapter provides case studies developed in five European small and medium-sized urban centres in intermediate and rural regions. While each of these five examples link culture and creativity with the improvement of tourism, they also seek to contribute to more sustainable forms of community development.